Real‐world practitioner perceptions of CARTITUDE‐4 results for patients with previously treated multiple myeloma - Alexandrina Balanean; Samuel Baird; Brooke Dulka; Luke Jennings‐Zhang; Robert N. Bone; Yolaine Jeune‐Smith; Bruce Feinberg; Muhamed Baljevic (eJHaem)
Abstract Introduction Initially approved for the fifth‐line or later therapeutic setting, the chimeric antigen receptor (CAR) T‐cell regimen ciltacabtagene autoleucel (cilta‐cel) was recently approved for second‐line (2L) treatment in relapsed/refractory multiple myeloma (RRMM). Oncology practitioners use clinical trials to inform treatment, but real‐world impressions and impact on practice are lacking. We aimed to determine whether presenting CARTITUDE‐4 clinical trial data would impact real‐world preferences/perceptions around CAR T‐cell therapy. Methods Recruiting from the Cardinal Health Oncology Provider Extended Network (OPEN), we surveyed hematologists/oncologists to investigate fourth‐line (4L) preferences in a hypothetical patient with triple‐class–refractory MM. We posed the same questions and answers before and after the trial presentation and compared pre‐/post‐preferences toward cilta‐cel and sequencing relative to bispecific antibodies (BsAbs). Using the same methodology as described above, we also performed a secondary analysis comparing pre‐/post‐perceptions on the use of CAR T‐cell therapy in earlier lines for patients with triple‐class–refractory MM. Results Among 50 respondents, decision‐making factors before the trial presentation included CAR T‐cell center availability (58%), comorbidities (52%), and center locations (34%). Additionally, 48% of 46 respondents chose 4L cilta‐cel. Among 47, 40% wanted more real‐world/long‐term CAR T‐cell therapy outcomes in any line, 38% wanted more 2L data, and 34% favored 2L/third‐line (3L) use. After the presentation, the preference for cilta‐cel doubled from 48% to 88% (p < 0.001) among 50 respondents and rose from 34% to 55% (p = 0.001) for earlier‐line CAR T‐cell therapy among 49. Moreover, 55% of 49 respondents preferred CAR T‐cell therapy prior to BsAbs. Discussion We have shown that making oncology practitioners aware of trials precipitated decision‐making factors and led to notable, significant shifts in future intended practice patterns. Being aware of trial data enables practitioners to make more informed decisions, tailor therapies to individual patients, and ultimately improve outcomes.